2014
DOI: 10.1016/j.bbr.2014.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopaminergic therapy on locomotor adaptation and adaptive learning in persons with Parkinson's disease

Abstract: Persons with Parkinson’s disease (PD) are characterized by multifactorial gait deficits, though the factors which influence the abilities of persons with PD to adapt and store new gait patterns are unclear. The purpose of this study was to investigate the effects of dopaminergic therapy on the abilities of persons with PD to adapt and store gait parameters during split-belt treadmill (SBT) walking. Ten participants with idiopathic PD who were being treated with stable doses of orally-administered dopaminergic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 45 publications
5
41
0
Order By: Relevance
“…Second, people with PD completed all data collection ON levodopa. Previous studies have indicated that levodopa may have positive [38], or perhaps negative [25] effects on learning depending on the type learning evaluated (i.e. explicit, implicit, upper or lower limb, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Second, people with PD completed all data collection ON levodopa. Previous studies have indicated that levodopa may have positive [38], or perhaps negative [25] effects on learning depending on the type learning evaluated (i.e. explicit, implicit, upper or lower limb, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…In individuals with Parkinson's disease, re-learning (savings) of an upper extremity movement is attenuated (Marinelli et al 2009;Bédard and Sanes 2011), similar to the young children in this study. However, savings of split-belt walking was recently found to be intact in Parkinson's disease (Roemmich et al 2014). New studies are needed to understand which brain networks are most important for development of mature re-learning patterns.…”
Section: Protracted Brain Development May Explain Attenuated Re-learnmentioning
confidence: 99%
“…Over several minutes of split-belt walking, interlimb parameters such as step length symmetry and double support time adapt (Reisman et al, 2005). Step length symmetry adaptation is a robust finding replicated in stroke survivors (Reisman et al 2007; Reisman et al 2013), Parkinson’s disease patients (Roemmich et al 2014a; Roemmich et al 2014b), and many conditions in healthy subjects (Malone, Bastian, 2010; Torres-Oviedo, Bastian, 2012; Torres-Oviedo, Bastian, 2010; Finley et al, 2014). During split-belt walking, ground reaction forces (GRF) exhibit predictive changes at initial contact, although vertical GRF in single support and propulsive GRF changes immediately, indicating reactive control (Mawase et al, 2013; Ogawa et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…However, changes in joint work during split-belt adaptation are largely unknown. Only ankle work in late stance and hip work in swing have been quantified in split-belt adaptation (Roemmich et al 2014a, Hinkel-Lipsker, Hahn, 2016). Furthermore, split-belt walking has not been tested on trans-tibial amputees.…”
Section: Introductionmentioning
confidence: 99%